THE IMPLEMENTATION LEVEL OF SEVEN EFFORTS OF PIG FARMING IN KACARIBU VILLAGE KABANJAHE SUBDISTRICT KARO REGENCY NORTH SUMATRA PROVINCE - E. K., Kacaribu; Inggriati, N. W. T.; Suarta, G. (Jurnal Peternakan Tropika; Vol 10 No 2 (2022): Vol. 10 No. 2 Tahun 2022; May - August, 2022)
This research aims to determine the level implementation level of seven efforts of pig farming and factors related to the implementation level of seven efforts of pig farming in Kacaribu Village. This research was conducted in Kacaribu Village, Kabanjahe District, Karo Regency, North Sumatra Province from August to September 2021. Determination of the research location by purposive sampling method , and the selection of respondents using the stratified random sampling of 45 people. Data analysis was carried out by means of qualitative descriptive and test Spearman’s Level Correlation Coefficient (Siegel, 1977). The results showed that the implementation level of seven efforts of pig farming in Kacaribu Village was in the medium category. Factors such as non-formal education, number of livestock ownership, income, knowledge, attitudes, skills and motivation of farmers have a very significant relationship (P<0.01) to the implementation level of seven efforts of pig farming, the factor of formal education of farmers has a significant relationship (P<0.05) to the implementation level of seven efforts of pig farming, the factors of age, land tenure, number of family dependents, and length of husbandry had no significant relationship (P>0.10) to the implementation level of seven efforts of pig farming. Conclusions: 1) The implementation level of seven efforts of pig farming in Kacaribu Village is in the medium category; 2) Factors related to the implementation level of seven efforts of pig farming are formal education, non-formal education, number of livestock ownership, income, knowledge, attitudes, skills, and motivation. Suggestion: to the relevant government, in order to improve the quality and quantity of counseling, training and guidance to further improve the knowledge, skills, attitudes and motivation of pig farmers. Keywords : factors, knowledge, correlation, counseling